Đánh giá sự tích lũy và rủi ro sinh thái một số kim loại nặng trong trầm tích cửa sông Hàn, Thành phố Đà Nẵng - Lê, Thị Trinh (Đại học Quốc gia Hà Nội, Việt Nam, 2017)
Deposited sediments contain toxic metals which can pollute surface water as well as aquatic eco-systems. Accumulation of heavy metals in sediment was assessed based on the geoaccumulation index (Igeo), the degree of contamination (Cd value) and potential ecological risk was also proposed based on ecological risk index (RI). The surface sediments collected at Han river estuary, Da Nang city were digested with a mixture of HNO3 nd H2O2, and analyzed for five heavy metals Cd, Cr, Cu, Pb and Zn sing inductively coupled plasma-atomic emission spectroscopy (ICP-AES), separately using the AAS method for AS .Â Results showed that all of metals were detected in sediment samples with mean concentration of As, Cd, Cr, Cu, Pb and Zn were 9.16; 0.083; 52.5; 45.4; 23.2 and 41.1 mg/kg dw, in respective. Cd values were smaller than 8 suggested that surface sediments of Han river estuary were moderately polluted by this metal.Â Besides, the results of potential ecological risk factor show that the risks of heavy metals are in the decreasing order of Cu>Pb>As>Cr>Cd>Zn.